2018
DOI: 10.1177/1077558718808709
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Affordable Care Act Medicaid Expansion on Disparities in Access to Care and Health Status

Abstract: Before the Affordable Care Act Medicaid expansion, nonelderly childless adults were not generally eligible for Medicaid regardless of their income, and Hispanics had much higher uninsured rates than other racial/ethnic subgroups. We estimated difference-in-differences models on Behavioral Risk Factor Surveillance data (2011-2016) to estimate the impacts of Medicaid expansion on racial/ethnic disparities in insurance coverage, access to care, and health status in this vulnerable subpopulation. Uninsured rates a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
66
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(76 citation statements)
references
References 38 publications
4
66
1
Order By: Relevance
“…In contrast to our physical health findings, we did not see significant changes in days of poor mental health or days of usual activities missed. Our findings differ from those of national serial crosssectional studies, which found improvements in poor mental health days and activity limitations in Medicaid expansion states compared with nonexpansion states 2. The Oregon Health Insurance Study also found reduced depression in the first 2 years after gaining Medicaid coverage 30.…”
contrasting
confidence: 99%
“…In contrast to our physical health findings, we did not see significant changes in days of poor mental health or days of usual activities missed. Our findings differ from those of national serial crosssectional studies, which found improvements in poor mental health days and activity limitations in Medicaid expansion states compared with nonexpansion states 2. The Oregon Health Insurance Study also found reduced depression in the first 2 years after gaining Medicaid coverage 30.…”
contrasting
confidence: 99%
“…The Medicaid program currently covers approximately 70 million people in the US, at an annual cost of approximately $600 billion, with increasing enrollment expected because of its expansion under the Affordable Care Act. [8][9][10] Although Medicaid has been demonstrated to improve access to services such as primary and preventive care, 11 some lines of evidence suggest that Medicaid may be suboptimal for the management of complex cancers that require specialist care. At least in part as a result of lower reimbursement, 12 access to specialized outpatient care has been shown to be limited by Medicaid coverage in children and adults.…”
Section: Introductionmentioning
confidence: 99%
“…Delayed access to the health care system has been found to increase the use of emergency rooms for nonurgent conditions [10][11][12] and, most important, has been assumed to negatively affect health outcomes due to delays in diagnosis and treatment. 13,14 Otorhinolaryngological problems are one of the most common reasons for hospital visits. Ear, nose, and throat (ENT) diseases are characterized by a broad spectrum of symptoms and physical features that may vary greatly in range and severity from case to case.…”
Section: Introductionmentioning
confidence: 99%